Isolation and Medicinal Applications of Clove Eugenol : Systematic Literature Review - Subakir Salnus (Hayyan Journal, 2025)
This review synthesizes research on "Good techniques for isolation and purification of chemical composition of clove compounds, focusing on eugenol, and their medicinal uses" to address inconsistencies in extraction efficacy and bioactivity preservation. The review aimed to evaluate extraction and purification methods for eugenol isolation, benchmark yield and purity, identify associated medicinal properties, compare conventional and green technologies, and analyze extraction parameters influencing bioactivity. A systematic analysis of studies employing hydro-distillation, Soxhlet, microwave-assisted, ultrasound-assisted, supercritical CO2, and deep eutectic solvent extractions was conducted, alongside chemical and chromatographic purification techniques. Findings indicate that microwave-assisted and ultrasound-assisted methods achieve higher eugenol yields (up to ~20%) and maintain bioactivity more effectively than conventional methods, while green technologies reduce solvent toxicity and energy consumption. Chemical purification attains high purity (>95%) but often compromises yield and sustainability. Analytical methods such as GC-MS and HPLC provide robust purity assessment, though standardization remains limited. Bioactivity assays confirm strong antioxidant, antibacterial, and antiinflammatory effects linked to extraction parameters and purity levels. Integration of extraction and purification processes is emerging but underdeveloped, with scalability and reproducibility challenges persisting. These findings underscore the need for standardized, sustainable protocols optimizing yield, purity, and medicinal efficacy of eugenol, informing future pharmaceutical and nutraceutical applications.